A Friendly Approach to Repair Fourth Degree Perineal Tears (Bangladesh Medical Journal, 2014)
To make the gynaecologists familiar with the procedure of continuous repair of rectal mucosa and repair the anal sphincter by other than figure of 8 suture and to compare the effectiveness of these procedures with the traditional procedures this study was planned. This was a observational comparative study. This study was carried out in one public medical college hospital and two private hospitals in Dhaka city and out side. Total 18 (Eighteen) patients were included in this study . Age, parity, residence were different but all had fourth degree perineal tear. Tears were repaired by traditional approach in half of the patients who were grouped under A and with the new approach in another half, grouped under B. Follow up was carried out at an interval of 6 weeks, 12 weeks, 24 weeks in both groups and the findings were compared. Among 18 patients a large number of women were mother of one child and were of 21 -25 years age group. At post operative period - wound infection was nil. Perineums were well established in all cases. On follow up at 24th week-pain in perineum and dyspareunia was nil in all cases, though this was present at early weeks in few cases. Faecal incontinence was absent in any patient by 24 weeks postoperatively. In early follow up periods there were some faecal incontinence, pain and dyspareunia in group A but les with group B. So, continuous repair of anal mucosa and repair anal sphincters other than figure of eight seems better regarding technical easiness, better compliance for the surgeon and less traumatic to the rectal mucosa and ultimately better results. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18803 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 31-33